Bacteremia in oncologic pediatric patients with febrile neutropenia at Chiang Mai University Hospital between 2007 and 2009 - Wangirapan, Anchalee; Natesirinilkul, Rungrote; Thanarattanakorn, Pattra; Charoenkwan, Pimlak (Biomedical Sciences and Clinical Medicine, 2024)
Objectives To identify causative organisms and the antimicrobial susceptibility pattern in oncologic pediatric patients with febrile neutropenia (FN). Methods A retrospective study in oncologic patients aged less than 18 years, who were admitted to the oncologic ward of the Department of Pediatrics, Chiang Mai University Hospital and diagnosed FN between January 2007 and December 2009. Results One hundred and forty six patients with 305 episodes of FN were included in this study. The most common underlying disease of the patients was acute lymphoblastic leukemia (45.6%). Only 30 episodes had positive hemoculture. Gram negative bacteria were the pathogens (86.7%) isolated most frequently. Three of the most common causative organisms were Acinetobacter baumannii (27.6%), Pseudomonas aeruginosa (16.7%) and Escherichia coli (10%), consecutively. Eighty eight percent of A. baumannii specimens were sensitive to colistin, but only 37.5% to piperacillin/tazobactam, ceftazidime and amikacin. P. aeroginosa and other Gram negative bacteria were still 100% sensitive to ceftazidime and amikacin, except for the extended spectrum of beta-lactamase bacteria and Stenotrophomonas maltophilia. The cure rate of treatment within the current guideline was 94.1%. However, the outcome of patients with A. baumannii septicemia was as high as 50% (4 of 8 patients). Conclusion A. baumannii is an emerging organism of FN among pediatric patients with malignancies in Chiang Mai University Hospital. Although the current FN guideline is still effective, carbapemen and colistin should be given early in pediatric FN patients who are at risk of A. baumannii bacteremia in order to reduce the mortality rate from this organism.